EFFICACY OF VAGAL NERVE STIMULATION IN IRAQI PATIENTS WITH REFRACTORY EPILEPSY: TWO-YEAR EXPERIENCE (Iraqi Journal of Medical Sciences, 2016)
Background:Refractory epilepsy patients who fail to respond to two antiepileptic drugs used appropriately are likely to have medically refractory seizure disorder and should be investigated for alternative forms of treatments like experimental drug trial, surgical treatment, electrical stimulation and combination of these. Vagal nerve stimulation is an adjunctive treatment for certain types of epilepsy.Objectives:To evaluate the efficacy of vagal nerve stimulation in refractory epilepsy, as an adjunctive therapy to antiepileptic drugs in Iraqi patients.Methods: A retrospective study recruiting 34 patients at Neurosciences Hospital in Iraq between Feb. 2008 and Jan. 2011. Diagnosed as refractory epilepsy according to International League Against Epilepsy criteria; the epilepsy state, number of the anti-epileptic drugs, frequency and severity of the attacks (using Chalfont scale) was assessed before and after the vagal nerve stimulation implantation. Programming was done every two weeks depending on clinical assessment.Results:Severity of the attacks was reduced totally 100% in 26.5% of the patients and 50-99% in 26.5% of patients. The number of attacks per month was decreased by 100% in 26.5% of patients and showed more than 50% improvement in 38% of patients. The number of the drugs used after the implantation decreased by 17.6% (P = 0.007). The most common side effects were hoarseness of voice 55.8% and dysphagia 41% only during the on time of the device.Conclusion: Vagal nerve stimulation is effective safe and well tolerated in Iraqi patients.Key words: Vagus nerve stimulation, Refractory epilepsy, Anti-epileptic drugs, Iraqis.
Keywords: Vagus nerve stimulation; Refractory epilepsy; Antiepileptic drugs; Iraqis